Asymptomatic Tumor Thrombus in the Left Atrium from Squamous Cell Carcinoma. (21st December 2021) - Huang, Nick; DiCorato, Christina; Abuzuaiter, Basel; May, Adriana; Deshmane, Swati P.; Chaudhuri, Debanik; Graziano, Stephen; Gambhir, Harvir Singh
Abstract : A 67-year-old female patient presented asymptomatically for further evaluation of a chest mass. Other than significant smoking history, the patient had been healthy with a recently treated case of uncomplicated pneumonia. The mass originated in the aortopulmonary window of the left mediastinum and invaded proximally into the left superior pulmonary vein and subsequently into the left atrium. The mass protrusion into the mitral valve occupied 50% of the left atrium space but showed no clinical symptoms of a valvular blockade. Poorly differentiated squamous cell carcinoma was identified upon biopsy. These findings of a primary lung tumor with atrial extension in an asymptomatic patient point to the importance of age-appropriate screening and standardization treatment modalities.